Betrayal in the poetry of the Andalusian Ibn Ammar - Oleiwi Hussein, Sahira (International Journal of Psychosocial Rehabilitation, 2020)
This research aspires to study treachery in the poetry of Al-Andalusian son of Ibn Ammar, to ask about the impact of the environment on the building of Ibn Ammar’s political and literary character, and to reveal the motives and reasons that made him prey to treason, as well as the explanation of treason from an Islamic perspective and their ontophanies with Ibn Ammar.